Memomath: Educational Game Application for Elementary School Children in Special Inclusion Classes for Students with Slow Learner Diagnosis - Trinovita Zuhara Jingga; Rina Novita; Ega Evinda Putri; Widya Febrina; Perdana Putera (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2024)
Memomath is a game-based educational application designed to support the learning of children diagnosed as slow learners in elementary school inclusion classes. This application integrates mnemonic-based math, reading, and memory exercises to improve students' academic skills and learning motivation. This research was conducted at SDIT Madani Islam Terpadu Kota Payakumbuh, an inclusive school that provides special programs for students with slow learning needs. The waterfall method was applied in the development of this application, involving the stages of needs analysis, design, implementation, testing, and maintenance. The test results showed that this application was effective in increasing engagement and understanding of concepts in students, especially at the age of 7-12 years. The data also revealed the relationship between age and duration of application use, providing important insights for design optimization. This study shows that a targeted gamification approach can make a significant contribution to the education of children with special needs, especially in helping them overcome learning challenges.